The foundations of Homeopathy and its use in the SUS: An integrative review (International Seven Journal of Health Research, 2023)
Introduction: The objective of this study is to evaluate the use of Homeopathy in the SUS, analyzing the existing prejudices and contrasting them with scientific results, using a literature review. Methodology: A narrative literature review was carried out  and the search for articles occurred through  the use of the descriptors inserted in the MeSH: "Homeopathy" and "Unified Health System". The Boolean operator "AND" was used between the combinations. The inclusion criteria were articles related to the selected descriptors, with English and Portuguese language and between 2007-2022. We found 8 articles in Scielo and 17 in pubmed, totaling 25 articles. Results: Homeopathy is a medicinal treatment and secular practice. However, despite being regulated by the SUS, homeopathic therapy is not widespread in Brazil, since there are difficulties in the development of research in the area, either due to methodological difficulties or financial support. Discussion: The low use of Complementary Therapies in the SUS may be associated with the lack of knowledge about such practices by health professionals, who in turn are unaware of the existence of the PNPIC, as well as the lack of disciplines that address this theme in undergraduate courses. Even though it is a practice used for more than two centuries in several countries, Homeopathy remains marginalized in the face of modern scientific rationality because it is based on unorthodox principles, which challenge the linear thinking characteristic of the paradigm of traditional science, which presupposes objectivity, stability and simplicity. Conclusion: Humanizing patient care, adopting preventive practices to cope with diseases, building a healthy life, recovering the understanding of the health-disease concept, are the principles that guide SUS policies and that meet the fundamentals of Homeopathy. In addition, its inclusion in the SUS makes it possible to expand the universe of users, configuring the citizen's right to choose. This work suggests more in-depth research on the subject and improvements in communication between health professionals.